Pergeseran Hukum Kewarisan Islam di Indonesia dengan Pemberian Wasiat Wajibah kepada Ahli Waris Non Muslim:Studi Kasus Putusan Mahkamah Agung No. 16K/Ag/2010 - Maman Suparman; Rd. Yudi Anton Rikmadani; Tubagus Ahmad Suhendar (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The existence of non-Muslim heirs in one family will cause problems when dividing the inheritance of the heirs. Islamic law firmly states that non-Muslim heirs are an obstacle to getting a share of the inheritance of the Muslim heirs. The research results obtained are that the ulama and jurists agree that religious differences between the Heir and the heir are one of the factors that hinder them from obtaining the right to be an heir, Muslims cannot accept infidels and vice versa. Non-Muslim heirs in the Islamic inheritance system in Indonesia can receive the heir's inheritance through a mandatory will based on a court decision, although the court decision is not binding on all Indonesian citizens, but only as a guide for future judges in deciding similar cases. However, there were pros and cons regarding this decision among fiqh experts and Islamic law academics. The ideal reconstruction model for distribution of inheritance for non-Muslim heirs in the Islamic inheritance system in Indonesia, namely by means of a mandatory will but given on the basis of expanding the meaning of Article 209 KHI, a mandatory will is given to non-Muslim heirs not from the inheritance but from the inheritance of the heir, and granting mandatory wills to non-Muslim heirs based on benefit, expediency and justice and given to non-Muslim heirs who are in dire need from an economic perspective.